Making and breaking of exciton cooling bottlenecks in halide perovskite nanocrystals - Lim, Melvin Jia Wei (2024)
Harnessing quantum confinement (QC) effects in semiconductors to retard hot carrier cooling (HCC) is an attractive approach for enabling efficient hot carrier extraction to overcome the Shockley–Queisser limit. However, there is a debate about whether halide perovskite nanocrystals (PNCs) can effectively exploit these effects. To address this, we utilized pump–probe and multipulse pump–push–probe spectroscopy to investigate HCC behavior in PNCs of varying sizes and cation compositions. Our results validate the presence of an intrinsic phonon bottleneck with clear manifestations of QC effects in small CsPbBr3 PNCs exhibiting slower HCC rates compared to those of larger PNCs. However, the replacement of inorganic Cs+ with organic cations suppresses this intrinsic bottleneck. Furthermore, PNCs exhibit distinct size-dependent HCC behavior in response to changes in the cold carrier densities. We attribute this to the enhanced exciton–exciton interactions in strongly confined PNCs that facilitate Auger heating. Importantly, our findings dispel the existing controversy and provide valuable insights into design principles for engineering QC effects in PNC hot carrier applications.